PROFILE OF TUBERCULOSIS CASES AMONG THE POPULATION DEPRIVED OF LIBERTY - de Nazaré Pereira Chagas, Denicy (2023)
Was to describe the profile of tuberculosis cases among the deprived population of Brazilian prisons, from 2014 to 2018, including regional and clinical factors. It carried out an ecological study, with the analysis of the trend in the prevalence of Tuberculosis in the prison population, considering the time frame from 2014 to 2018. Data were obtained from the Information System for Notifiable Diseases. Reflect a worrying panorama of tuberculosis among the population deprived of liberty in the Brazilian context, together with the high prevalence of HIV/aids and the consumption of alcohol and other drugs, comorbidities that affect the diagnosis and treatment of tuberculosis and that there are gaps in the control and monitoring of the disease. And permanent educational actions for the prevention, protection and promotion of their health are necessary, in order to minimize the potential risks of illnesses caused by tuberculosis in Brazilian prisons.